The Role of Fiqh al-Siyar in International Law-Making: Escaping the Lethargy - Fajri Matahati Muhammadin; Shania Dwini Azzahra (Al-Jami'ah: Journal of Islamic Studies, 2022)
International law has developed since its pre-20th century consent-based positivistic framework to ‘international law-making’ where the role of state sovereignty is seen to have eroded. This development, however, still reproduces its pre-20th century colonialist features against non-European (including Islamic) legal thought, pushing them to the peripheries of relevance. Recently, countering that, stronger voices have demanded international law to generally include non-European and specifically Islamic international legal scholarship. However, while having a very rich body of classical scholarship, contemporary literature of fiqh al-siyar (Islamic international law) suffers from lethargy. It neither mentions nor responds to the trend of international law-making. This article, employing a literature-based research approach, bridges the gap of that lethargy so that fiqh al-siyar could develop to properly respond to the current trend of international law-making. It is found that fiqh al-siyar must critically adopt and respond to the features of international law-making, and all actors must utilize all channels to participate in its process.[Hukum Internasional telah berkembang jauh sebelum abad 20 dalam kerangka dasar isi yang positivistik dalam pembentukannya, dimana peran kedaulatan negara mulai terlihat berkurang. Hal ini terus berkembang sampai berwajah kolonial yang mengabaikan dan meminggirkan hukum non Eropa, termasuk hukum Islam. Namun akhir-akhir ini muncul suara yang menginginkan bahwa hukum internasional harus mengakui secara umum hukum non Eropa dan khususnya pemikiran hukum Internasional Islam. Alih alih memberikan kontribusi dalam pemikiran klasik, literatur kontemporer hukum internasional Islam (fiqh al-siyar) justru mengalami kelesuan. Bukan hanya tidak disebut tapi juga tidak merespon perkembangan hukum internasional. Dengan pendekatan kajian literatur, tulisan ini berusaha menjembatani kesenjangan kelesuan tersebut agar hukum internasional Islam (fiqh al-siyar) dapat berkembang dan merespon dengan baik trend saat ini. Selain itu, fiqh al-siyar harus secara kritis dalam mengadopsi dan merespon perkembangan hukum internasional, serta semua aktor harus mendayagunakan semua saluran untuk terlibat dalam proses tersebut.]